Pengembangan eBook Bergambar Cerita Rakyat Berbahasa Inggris untuk Mendukung Pembelajaran Teks Naratif Berbasis Kearifan Lokal - Natalina Asi; Iwan Fauzi (IKIP PGRI Pontianak, 2023)
This research belongs to research and development method which aims to gain a product and to test its effectiveness. The research and development model used is the 4D model named for Define, Design, Development, and Dissemination. The product yield is a digital book (eBook) of Central Kalimantan folklore with pictures in English to support narrative text learning material in the junior high school level. The school chosen as the try out sample for the product was SMP Negeri-2 Palangka Raya by choosing two English teachers and 72 students. The results showed that the product design has met the feasibility standardization in terms of media form, material content, and language use. In addition, after being tested, the product developed is able to improve student learning outcomes in terms of understanding the social function of the text, generic structure, and language features as illustrated in the pictured narrative texts. Thus, the eBook has made a positive contribution to student learning achievement because it has supported the implementation of learning and made it easier for students to achieve the competency that they must attain.